A Randomized Trial on the Effect of Phosphate Reduction on Vascular End Points in CKD (IMPROVE-CKD) - Toussaint, Nigel D.; Pedagogos, Eugenia; Lioufas, Nicole M.; Elder, Grahame J.; Pascoe, Elaine M.; Badve, Sunil V.; Valks, Andrea; Block, Geoffrey A.; Boudville, Neil; Cameron, James D.; Campbell, Katrina L.; Chen, Sylvia S.M.; et al. (Journal of the American Society of Nephrology, 2020)
Hyperphosphatemia is associated with increased fibroblast growth factor 23 (FGF23), arterial calcification, and cardiovascular mortality. Effects of phosphate-lowering medication on vascular calcification and arterial stiffness in CKD remain uncertain. To assess the effects of non-calcium-based phosphate binders on intermediate cardiovascular markers, we conducted a multicenter, double-blind trial, randomizing 278 participants with stage 3b or 4 CKD and serum phosphate >1.00 mmol/L (3.10 mg/dl) to 500 mg lanthanum carbonate or matched placebo thrice daily for 96 weeks. We analyzed the primary outcome, carotid-femoral pulse wave velocity, using a linear mixed effects model for repeated measures. Secondary outcomes included abdominal aortic calcification and serum and urine markers of mineral metabolism. A total of 138 participants received lanthanum and 140 received placebo (mean age 63.1 years; 69% male, 64% White). Mean eGFR was 26.6 ml/min per 1.73 m ; 45% of participants had diabetes and 32% had cardiovascular disease. Mean serum phosphate was 1.25 mmol/L (3.87 mg/dl), mean pulse wave velocity was 10.8 m/s, and 81.3% had abdominal aortic calcification at baseline. At 96 weeks, pulse wave velocity did not differ significantly between groups, nor did abdominal aortic calcification, serum phosphate, parathyroid hormone, FGF23, and 24-hour urinary phosphate. Serious adverse events occurred in 63 (46%) participants prescribed lanthanum and 66 (47%) prescribed placebo. Although recruitment to target was not achieved, additional analysis suggested this was unlikely to have significantly affected the principle findings. In patients with stage 3b/4 CKD, treatment with lanthanum over 96 weeks did not affect arterial stiffness or aortic calcification compared with placebo. These findings do not support the role of intestinal phosphate binders to reduce cardiovascular risk in patients with CKD who have normophosphatemia. Australian Clinical Trials Registry, ACTRN12610000650099.